2010
DOI: 10.1593/neo.10486
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate Receptor GRIA3—Target of CUX1 and Mediator of Tumor Progression in Pancreatic Cancer

Abstract: Previously, we identified the transcription factor CUX1 as an important modulator of invasion and resistance to apoptosis. Expression profiles suggested that CUX1 regulates a complex transcriptional program mediating tumor progression. We aimed to identify functionally relevant targets of CUX1 by using RNA interference (RNAi)-based loss-of-function screens. Therefore, we generated an RNAi library containing putative transcriptional targets of CUX1 identified by microarrays and performed cell viability screens.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 25 publications
1
29
1
1
Order By: Relevance
“…GRIA3 is a subunit of ionotropic glutamate receptors (AMPAR) [39] and was shown to promote tumor progression in glioma [49, 50] and pancreatic cancer [39]. In this study, western blotting and qRT-PCR demonstrated that GRIA3 level was inversely correlated with miR-330-3p expression.…”
Section: Discussionmentioning
confidence: 66%
“…GRIA3 is a subunit of ionotropic glutamate receptors (AMPAR) [39] and was shown to promote tumor progression in glioma [49, 50] and pancreatic cancer [39]. In this study, western blotting and qRT-PCR demonstrated that GRIA3 level was inversely correlated with miR-330-3p expression.…”
Section: Discussionmentioning
confidence: 66%
“…These findings together with the observation that CUX1 expression is elevated in breast tumors of higher histopathological grade as well as in pancreatic cancer tissues led to the suggestion that CUX1 plays a role in tumor progression (Michl et al, 2005;Ripka et al, 2010a). The Src tyrosine kinase, the WNT5A ligand and the glutamate receptor GRIA3 were shown to be regulated downstream of CUX1 and to mediate some of its effects (Aleksic et al, 2007;Ripka et al, 2007;Ripka et al, 2010b). Whether elevated CUX1 expression, as observed in many human cancers, could stimulate cell motility remained to be verified.…”
Section: Cux1 Regulates Many Genes Involved In Cell Motilitymentioning
confidence: 99%
“…Studies in various tumor cell types have identified many CUX1-regulated genes, whether direct targets or not, that could contribute to tumorigenicity (Michl et al, 2005;Amiri et al, 2006;Ueda et al, 2007;Harada et al, 2008;Truscott et al, 2008;Cadieux et al, 2009;Kedinger et al, 2009;Siam et al, 2009;Ripka et al, 2010b;Kojima et al, 2011;Sansregret et al, 2011). It is likely that the role of CUX1 in tumor initiation and progression involves a large number of genes that play a role in multiple biological processes (Luo et al, 2009).…”
Section: Targets Of Cux1 That Contribute To Tumorigenesismentioning
confidence: 99%
“…Pathway analysis of the total of 339 genes showed that altered genes are largely involved in cell division and cell cycle regulation (Table 1). For two hypermethylated genes in our analysis, ESX1, a homeodomain protein, was reported to regulate cell cycle progression and transcription [24-26], and GRIA3 has been shown to promote proliferation in nonneuronal cells [27, 28]. As other glutamate receptors, such as NMDA receptor, have an important function in podocyte biology and glomerular diseases, we selected GRIA3 for further analysis.…”
Section: Resultsmentioning
confidence: 99%